2019
DOI: 10.1093/sleep/zsz110
|View full text |Cite
|
Sign up to set email alerts
|

Effects on resident work hours, sleep duration, and work experience in a randomized order safety trial evaluating resident-physician schedules (ROSTERS)

Abstract: Study Objectives We compared resident physician work hours and sleep in a multicenter clustered-randomized crossover clinical trial that randomized resident physicians to an Extended Duration Work Roster (EDWR) with extended-duration (≥24 hr) shifts or a Rapidly Cycling Work Roster (RCWR), in which scheduled shift lengths were limited to 16 or fewer consecutive hours. Methods Three hundred two resident physicians were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 19 publications
(29 reference statements)
1
31
0
7
Order By: Relevance
“…With increased number of duty days rostered in a week, being associated with greater levels of fatigue and a rise in perception of safety being compromised due to fatigue. Research in the healthcare industry has found that reducing the number of shifts and/or consecutive work hours for doctors improves sleep duration [64] and significantly lowers the number of medical errors [65]. The aviation industry may apply similar changes, such as introducing more rest days between trips to reduce fatigue and sleepiness.…”
Section: Future Directionsmentioning
confidence: 99%
“…With increased number of duty days rostered in a week, being associated with greater levels of fatigue and a rise in perception of safety being compromised due to fatigue. Research in the healthcare industry has found that reducing the number of shifts and/or consecutive work hours for doctors improves sleep duration [64] and significantly lowers the number of medical errors [65]. The aviation industry may apply similar changes, such as introducing more rest days between trips to reduce fatigue and sleepiness.…”
Section: Future Directionsmentioning
confidence: 99%
“…As we reported elsewhere, under the EDWR, resident-physicians slept significantly less (mean 6 SD, 47.5 6 4.5 hours per week) as compared with the RCWR (49.1 6 4.9 hours per week). 23 Importantly, the distribution of sleep loss relative to work was also altered: During the EDWR, 10% of work hours were preceded by #2 hours of sleep in the preceding 24 hours, as compared with only 4% during the RCWR. Furthermore, the percentage of work hours preceded by $8 hours of sleep in the last day was higher during the RCWR (38%) than the EDWR (23%).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the percentage of work hours preceded by $8 hours of sleep in the last day was higher during the RCWR (38%) than the EDWR (23%). 23 The direct demonstration of a significant correlation between attentional failures as measured by the PVT and medical errors is important because the PVT is easier to measure and has been used extensively to evaluate the impact of work schedules on performance. The correlation observed between this laboratory measure and the risk of medical errors is consistent with a previous meta-analysis revealing that 24 hours of sleep loss had a similar impact on laboratory measures of performance in nonphysicians as it did on clinical…”
Section: Discussionmentioning
confidence: 99%
“…One schedule cohort involved daytime and nighttime work shifts limited to a maximum of 16 hours of duration, whereas the second involved traditional extended duration (>24 hr) work shifts, with daytime shifts alternating with extended duration work shifts every fourth night. On average, residents worked about 10% more hours per week on the extended duration work schedule ( 5 ). Throughout this article, we refer to these differing schedule cohorts as “short call” and “long call”.…”
Section: Methodsmentioning
confidence: 99%